Pengembangan Usaha Mikro Melalui Optimalisasi Media Sosial : Studi pada Lapak kece Palu. - Eka Andani; Mohammad Adrian; Nasilla Handayaningrum; Rian Rachdiat Maka; Siska Amaliah; Nuraisyah Nuraisyah; Syarif Permana Salingkat; Gita Farista (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study examines the development of a small business, Lapak Kece Palu, which started as an online shop and grew through social media optimization. The research aims to understand the motivation behind the business, the operational management, and the challenges faced by the owner. This qualitative descriptive study uses interview data to explore business background, management strategies, and obstacles related to capital and market expansion. Findings indicate that social media—particularly Instagram—plays a significant role in enhancing market reach through content creation, advertisements, and giveaway strategies. Challenges mainly relate to limited capital, which restricts product variety and inventory expansion. The study highlights the importance of digital marketing for sustaining micro- enterprise growth.